Complex Nonlinear Behavior in the Bromate–2‐Aminophenol Reaction. Issue 1 (9th November 2016) - Tang, Alexander; Bell, Jeffrey G.; Green, James R.; Wang, Jichang
ABSTRACT: The bromate–2‐aminophenol reaction in a batch reactor was investigated in this research, in which both simple and sequential oscillations were observed. The occurrence of sequential oscillations were found to be very sensitive to changes of the initial concentrations, where decreasing the concentration of sulfuric acid or sodium bromate or increasing the 2‐aminophenol concentration caused the two oscillation windows to coalesce. Lowering the reaction temperature from 30 to 5°C also caused the two oscillation windows to merge into one. A phase diagram in the bromate–sulfuric acid concentration plane demonstrates that sequential oscillations only occur within a narrow band of conditions. Mechanistic studies of the system through employing 1 H NMR and mass spectrometry suggest that a dibrominated ortho‐benzoquinone is a major product. The oxidation of 2‐aminophenol, on the other hand, can lead to the formation of pyrocatechol, which may be the substrate responsible for the second set of oscillations.